The Influence of Education Level, Income, and Consumption on Poverty in Tuban Regency - Rohmat, Rohmat; Subroto, Waspodo Tjipto; Sakti, Norida Canda (JPEKA: Jurnal Pendidikan Ekonomi, Manajemen dan Keuangan, 2024)
This study aims to analyze poverty in Tuban Regency which includes Effect of education level, income and consumption on partial and simultaneous poverty. The method used is a quantitative method with multiple regression analysis techniques. The sampling technique uses purposive sampling technique. Data used secondary data from Statistics of Tuban Regencys in 2008-2016, which includes data on education level, income, consumption and poverty. The results of the research. There is a significant effect between the education level on poverty, because the significant value of the education level variable is smaller than 0.050 which is equal to 0.037. There is no significant effect between income on poverty, because the significant value of the income variable is greater than 0.050 which is equal to 0.365. There is no significant effect between consumption on poverty, because the significant value of the consumption variable is greater than 0.050 which is equal to 0.094. There is a significant effect together between education level, income, and consumption on poverty, because the significant value is smaller than 0.050 which is equal to 0.001 so this result shows that the independent variable has a significant effect on the dependent variable together.